NEW CELLULOSIC-BASED ACOUSTIC WALL BOARD MATERIAL FROM PAPER WASTE - Razali, Luqman Hakim (Universiti Teknologi Petronas, 2011)
Paper waste is a common pollution that encounter by the world nowadays. The paper industry ranks 4th in contribution to greenhouse gas emissions, and contribute 9% of the manufacturing sector's carbon emissions. Facts show that typical business office will produce about 1.5 pounds of paper waste per employee each day. Increase in generation of the paper waste around the world, especially in developing countries, has created a need to develop new ways to use this waste to obtain value-oriented products. Due to unlimited amount of waste that being produced every day, recycling it would be a tremendous solution. Paper waste is a rich source of cellulose, which can be chemically modified to produce valuable products. With certain composite combination, the properties of a paper can be enhanced and flexible. The purpose of this proposal is to represent an introduction about the project and state the problem along with the objectives and methodology used to solve the problem. The first chapter makes brief introduction about the project. The report continues with the second chapter, which is literature review. Then it is followed by methodology. The objective of the research is to study the effect of the combination of fiber and pulp to produce a new cellulosic material. It also observes the strength of the material of different fiber's orientation. The study focuses on two points, which are: the properties of the new cellulosic material after combined with fiber and the best fiber's orientation to use as an acoustic wall. The new cellulosic material will undergoes certain test and the result will determine the advantage of fiber used in recycled paper. The characteristic of the fiber will be discuss more in second chapter.